Exercise Intolerance in Post-Acute Sequelae of COVID-19 and the Value of Cardiopulmonary Exercise Testing- a Mini-Review - Aparisi, Álvaro; Ladrón, Raquel; Ybarra-Falcón, Cristina; Tobar, Javier; San Román, J. Alberto (Frontiers in Medicine, 2022)
Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus, with systemic organ damage in the most severe forms. Long-term complications of SARS-CoV-2 appear to be restricted to severe presentations of COVID-19, but many patients with persistent symptoms have never been hospitalized. Post-acute COVID-19 syndrome (PASC) represents a heterogeneous group of symptoms characterized by cardiovascular, general, respiratory, and neuropsychiatric sequelae. The pace of evidence acquisition with PASC has been rapid, but the mechanisms behind it are complex and not yet fully understood. In particular, exercise intolerance shares some features with other classic respiratory and cardiac disorders. However, cardiopulmonary exercise testing (CPET) provides a comprehensive assessment and can unmask the pathophysiological mechanism behind exercise intolerance in gray-zone PASC. This mini-review explores the utility of CPET and aims to provide a comprehensive assessment of PASC by summarizing the current evidence.